AB1358 Infectious antibodies repertoire in rheumatoid arthritis. (12th June 2018) - Schmiedl, A.; Reuter, S.; Lerner, A.; Brunner, S.; Schwarting, A.; Matthias, T.
Abstract : Background: The incidence of infectious diseases in the RA ADAPTHERA study by ELISA antibody screening and the differences in infectious distribution in active or low active disease patients was explored. Methods: Sera from 88 naive RA patients out of the ADAPTHERA study cohort, disease duration <6 months, were tested for antibody titers against: Herpes simplex virus 1 and 2 (HSV1 +2, IgG and IgM) Helicobacter pylori (HP, IgA and IgG), Cytomegalovirus (CMV, IgG and IgM), Toxoplasma gondii (Toxo, IgG), Adenovirus (IgG and IgM), Epstein Barr virus (EBV, IgG and IgM), and Parvovirus B19 (P-B19, IgG) were determined by using NovaLisa from NovaTec Immundiagnostica GmbH, GERMANY. Borrelia (IgG and IgM) titers were determined by AESKULISA and confirmed by Western blot ( AESKUBLOTS ) by AESKU.DIAGNOSTICS GmbH and Co. KG, GERMANY. Results: 82% RA patients were found to be positive for HSV1 +2 IgG (2% IgM positive), 8% for Adenovirus (IgA), 77% (IgG), and 1% (IgM). 99% for EBV-IgG (no IgM positive). 53% (IgG), and 26% (IgM) for CMV. 38% for HP-IgG and 15% for IgA and 79% for P-B19-IgG (3% IgM). 6% for Borrelia-IgM and 14% for IgG. A slightly increase was found for EBV sera positivity (99% IgG), compared to the normal population. Conclusions: Limited evidence exists regarding the impact of the disease activity on the susceptibility for infections, possibly due to the close association of RA disease activity and therapy dependent dosage of immunosuppressive treatment. Still, some infections may present memory contact, presenting an epiphenomenon. On the contrary, they might play an active role in RA pathophysiology. Disclosure of Interest: None declared